Belonging at a liberal arts college: Creating emotional and physical spaces of home (Comparative & International Education Series, 2021)
Research on international students’ experience has shown that a “sense of belonging,” friendships and socialization are critical to international students’ lived experience, especially since they face unique transitional and cross-cultural challenges.  This chapter examines the innovative programming approach of the Office of International Services (OIS) at a small, residential U.S. liberal arts college. Beyond providing immigration advising functions, OIS centers community building and empowerment as cornerstones of international students’ experience and education. Using narrative description and anecdotal accounts, this chapter explores the vital role innovative programming plays in creating spaces of ‘home’ for international students, highlighting three specific examples: a highly student-centered and student-driven international orientation; a Thanksgiving program that empowers students to co-create a shared experience and tradition; and an international development collaborative that allows students to grapple with the challenges and responsibilities of global citizenship.